A disposable biosensor based on immobilization of laccase with silica spheres on the MWCNTs-doped screen-printed electrode - Li Yuanting; Zhang Li; Li Meng; Pan Zhigang; Li Dawei (Chemistry Central Journal, 2012)
Abstract Background Biosensors have attracted increasing attention as reliable analytical instruments in in situ monitoring of public health and environmental pollution. For enzyme-based biosensors, the stabilization of enzymatic activity on the biological recognition element is of great importance. It is generally acknowledged that an effective immobilization technique is a key step to achieve the construction quality of biosensors. Results A novel disposable biosensor was constructed by immobilizing laccase (Lac) with silica spheres on the surface of multi-walled carbon nanotubes (MWCNTs)-doped screen-printed electrode (SPE). Then, it was characterized in morphology and electrochemical properties by scanning electron microscopy (SEM) and cyclic voltammetry (CV). The characterization results indicated that a high loading of Lac and a good electrocatalytic activity could be obtained, attributing to the porous structure, large specific area and good biocompatibility of silica spheres and MWCNTs. Furthermore, the electrochemical sensing properties of the constructed biosensor were investigated by choosing dopamine (DA) as the typical model of phenolic compounds. It was shown that the biosensor displays a good linearity in the range from 1.3 to 85.5 μM with a detection limit of 0.42 μM (S/N = 3), and the Michaelis-Menten constant (Kmapp) was calculated to be 3.78 μM. Conclusion The immobilization of Lac was successfully achieved with silica spheres to construct a disposable biosensor on the MWCNTs-doped SPE (MWCNTs/SPE). This biosensor could determine DA based on a non-oxidative mechanism in a rapid, selective and sensitive way. Besides, the developed biosensor could retain high enzymatic activity and possess good stability without cross-linking reagents. The proposed immobilization approach and the constructed biosensor offer a great potential for the fabrication of the enzyme-based biosensors and the analysis of phenolic compounds.